Controlling spatial forest structure with spatial simulation in forest management planning: a case study from Turkey - Kadiogullari, Ali Ihsan; Keles, Sedat; Baskent, Emin Zeki; Bingol, Ozkan (Universiti Kebangsaan Malaysia, 2015)
Decision Support Systems (DSS) is widely used to develop spatially explicit forest management plans through the integration of spatial parameters. As a part of this study, a simulation-based spatial DSS, the ETÇAPSimülasyon program was developed and tested in a case study area. The system has the capability to control the spatial structure of forests based on a geodatabase. Geographical Information Systems (GIS) was used to generate the database, using spatial parameters including opening size, block size and green-up delay in addition to other attribute data such as the empirical yield table and the product assortment table. Based on the simulation technique, a spatial forest management model was developed to link strategic planning with tactical planning on a stand base and to present results with a number of performance indicators. One important component of the model determined all spatial characteristics with spatial parameters and patch descriptions. A stand growth and yield simulation model (BARSM) based on the relationship between current and optimal basal area development was also generated to project future stand characteristics and analyze the effects of various silvicultural treatments. A number of spatial forest management strategies were developed to generate spatially implementable harvest schedules and perform spatial analyses. The forest management concept was enhanced by employing a spatial simulation technique to help analyzing the ecosystem structure. Spatial characteristics for an on-the-ground forest management plan were then developed. The model was tested in Altınoluk Planning Unit (APU) using a spatial simulation technique based on various spatial parameters. The results indicated that the spatial model was able to satisfy the spatial restriction requirements of the forest management plan.